The Ageing of Materials and Structures Towards Scientific Solutions for the Ageing of Our Assets - van Breugel, Klaas; Koleva, Dessi; Beek, Ton van.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This work is an overview of the state of art on Ageing of Materials and structures in the world. Ageing of materials is a natural phenomenon. Each material we use will age. This ageing will influence the performance of the object where the materials is used. Furthermore, the ageing will be affected by the surroundings in which the object is placed. The main focus of the book is on materials used in infrastructure, energy, buildings and industry. The book in effect establishes the definition of ageing and its main research topics that are relevant for society.
Chapter 1. Urgency and Challenges of Ageing in Science and Engineering -- Chapter 2. Investigation of Long-Term Behaviour of Elastomeric Seals for Transport and Storage Packages -- Chapter 3. What Can be Learnt from Ageing in Biology and Damage-Tolerant Biological Structures for Long-Lasting Biomimetic Materials? -- Chapter 4. Mechanics of Ageing-from Building to Biological Materials -- Chapter 5. The Relevance of Ageing for Civil Infrastructure: The Profession, The Politics, The Classroom -- Chapter 6. Study on Triage for Deteriorated Concrete Structures by JSCE-342 -- Chapter 7. Ageing in Shallow Underground RC Culverts and Tunnels -- Chapter 8. Radiation Shielding Properties and Freeze-Thaw Durability of High-Density Concrete for Storage of Radioactive Contaminated Soil in Fukushima -- Chapter 9. Ageing Behaviour of Neutron/Irradiated Eurofer97 -- Chapter 10. Ageing Management for Extended Storage of Spent Nuclear Fuel -- Chapter 11. Forever Young or Ageing Naturally? -- Chapter 12. The NoblePatina of Age -- Chapter 13. The Ageing of the Creation -- Chapter 13. Modeling Ageing Cementitious Pore Structure -- Chapter 14. Introduction to Structural Ageing-Specific Functions for Computational Models Based on Synaptic Networks -- Chapter 15. Stochastic Models for Risk and Failure under Ageing -- Chapter 16. Statistical Models for Interval-Censored Time-to-Event Data.
Keywords: Buildings -- Repair and reconstruction; Buildings -- Maintenance; Building materials; Polymers; Cultural property; Building Repair and Maintenance; Structural Materials; Polymers; Cultural Heritage